Soft tissue, pelvic, and urinary bladder leiomyosarcoma as second neoplasm following hereditary retinoblastoma. Issue 3 (1st March 2003) - Venkatraman, L; Goepel, J R; Steele, K; Dobbs, S P; Lyness, R W; McCluggage, W G
Abstract : This report describes two patients who developed leiomyosarcomas, one involving the subcutaneous tissue of the thigh and the pelvic soft tissues and the other the urinary bladder, following hereditary retinoblastoma 36 and 38 years earlier, respectively. There is an increased risk of the development of sarcoma, most commonly osteosarcoma, as a second malignancy following hereditary retinoblastoma. Leiomyosarcoma developing as a second malignancy has rarely been reported and most have occurred in the field of previous radiotherapy. The literature on leiomyosarcoma occurring as a second neoplasm following retinoblastoma is reviewed.